Gerakan Sosial Ekonomi Islam Di Pedesaan: Studi Kasus Peran Baitul Maal Wat Tamwil Di Kabupaten Sragen - Thohir Yuli Kusmanto (AL-TAHRIR, 2016)
Abstract: Islamic economic system has been experiencing rapid growth and development in Indonesia since the 1998 reform. Islamic economic discourse has become an intensive study, discussions, seminars, workshops to formulate ideal type of Islamic economics. Islamic economics is practically manifested in the form of banking, non-banking, insurance, and financial institutions. Islamic Economics has gone into rural areas in the systemic struggle among traditional economic system, a market economy and capitalistic system. Economic position of Islam becomes a middle way in terms of foundation, practices, access and capital assets. The seep of Islamic economy in the rural area is done through Baitul Maal Wat Tamwil (BMT). The process is viewed as a social movement so that it can touch rural communities. Its movement is performed by Islamic activist organizations of young generation which is affiliated with Islamic organizations or mosque activists. Early initiation was triggered by Center Incubation of Small Scale Business (Pusat Inkubasi Bisnis Usaha Kecil /PINBUK), Economic Organization, and Indonesian Muslim Scientist Association (Ikatan Cendekiawan Muslim/ ICMI) 1996. The establishment of BMT in Sragen was first done by Sragen ICMI branch. In this case, social and political conditions determined the process of formation. The primary role of BMT is as a financial institution and deposit. The role of financing has helped micro scale group of entrepreneurs,and  small and medium scale groups of entrepreneurs to develop their business, and access capital. BMT encourages rural people to save their money for investment. As the Islamic financial services cooperation, BMT teaches the spirit of brotherhood and cooperation to develop Islamic economy in the rural areas.   الملخص: أصبح النظام الإقتصادي الإسلامي ينمو نموّا سريعا في إندونيسيا بعد واقعة " إصلاح " 1999م. وأصبح حديث الإقتصاد الإسلامي موضوع دراسات متواصلة، ومناقشات علمية، وندوات، وورشات عمل لصياغة النموذج الأمثل للإقتصاد الإسلامي. ويتجلّى الإقتصاد الإسلامي عمليا في عدّة أشكال : المصرفية، وغير المصرفية، والتأمين والمؤسسات المالية. وقد تسرّب الإقتصاد الإسلامي في القرى في النضال النظامي بين الإقتصاد التقليدي وبين نظام الإقتصاد السوقي الرأسمالي، وأصبح الإقتصاد الإسلامي وسيطا في الأمور : الأساس والتطبيق والتدبير وعملية الحصول على الأصول والرأسمال. ويكون تسرّب الإقتصاد الإسلامي في القرى عن طريق بيت المال والتمويل. وهذه العملية كحركة إجتماعية حتى وصلت إلى المجتمع الريفي. وهذه الحركة قام بها مجموعة من الشبان المتحمّسين (أي الشبان الحركيين للمسجد) من المنظّمات الإسلامية  المنتمية إلى الجمعيّات الإجتماعية الإسلامية . كان الاستهلال الأول PINBUK   وهي المنظمة الإقتصادية لرابطة المثقّفين المسلمين الإندونيسيين (ICMI) سنة 1999م. وتأسيس بيت المال والتمويل في سراغين حرّكتها (ICMI) سراغين. والوضع الإجتماعي السياسي في ذلك الحين دفع عملية التشكيل. وكان دور بيت المال والتمويل الرئيس هو كمؤسسة التمويل والادّخار. ودوره التمويل يساعد العمل التجاري الصغير والمتوسّط لتنمية عمله التجاري وللحصول على الرأسمال. وقد حثّ بيت المال والتمويل المجتمع القروي على الادّخار للتمويل. وكمؤسسة الخدمات المالية الإسلامية، علّم بيت المال والتمويل الناس روح الأسرية والتعاون والتكافل لتنمية الإقتصاد الإسلامي في القرى Abstrak: Sistem ekonomi Islam mengalami pertumbuhan dan perkembangan yang pesat di Indonesia pasca reformasi 1998. Wacana ekonomi Islam telah menjadi kajian intensif, diskusi, seminar, lokakarya dan workshop merumuskan tipe ideal ekonomi Islam. Secara praktis ekonomi Islam mewujud dalam bentuk; perbankan, non bank, asuransi, dan lembaga keuangan. Ekonomi Islam telah meresap ke pedesaan diantara pergulatan sistemik, ekonomi tradisional dengan ekonomi pasar – kapitalistik. Posisi ekonomi Islam menjadi jalan tengah dalam hal; landasan, praktik, pengelolaan dan akses serta aset permodalan. Peresapan ekonomi Islam di pedesaan melalui Baitul Mal Wat Tamwil (BMT). Proses tersebut  sebagai suatu gerakan sosial, sehingga mampu menyentuh masyarakat pedesaan. Gerakannya dilakukan oleh generasi muda aktifis organisasi Islam yang berafiliasi dengan ormas Islam atau aktifis masjid. Inisiasi awal oleh Pusat Inkubasi Bisnis Usaha Kecil (PINBUK), organisasi ekonomi Ikatan Cendekiawan Muslim Indonesia (ICMI) tahun 1996. Pembentukan BMT di Kabupaten Sragen pertama kali digerakkan ICMI cabang Sragen. Kondisi sosial politik menentukan proses pembentukan. Peran utama BMT adalah sebagai lembaga pembiayaan dan simpanan. Peran pembiayaan telah menolong kelompok usaha mikro, kecil dan menengah mengembangkan usahanya, dalam mengakses permodalan. BMT mendorong masyarakat pedesaan menabung untuk investasi. Sebagai koperasi jasa keuangan syariah, BMT mengajarkan semangat kekeluargaan dan kerjasama untuk mengembangkan ekonomi yang Islami di pedesaan.